A new species of Brazilian Dendrocephalus (Anostraca, Thamnocephalidae) - Rabet, Nicolas (Zootaxa, 2006)
Dendrocephalus thieryi nov. sp., discovered in the state of Minas Gerais, Brazil, is described. The new species is defined by a unique morphology of its male frontal appendage and of the endopodites of the first four thoracopods. A dichotomous key to all known Dendrocephalus species based on male morphology is presented.